2009
DOI: 10.1007/s00167-009-0844-7
|View full text |Cite
|
Sign up to set email alerts
|

Double-bundle versus single-bundle ACL reconstruction using the horizontal femoral position: a prospective, randomized study

Abstract: The aim of this study was to evaluate whether anterior cruciate ligament (ACL) reconstruction using the double bundle technique (DB) improves stability in the knee compared with the single bundle technique (SB) with the femoral tunnel in a more horizontal position (2 or 10 o'clock). We conducted a randomized, prospective study. Forty patients were randomized to the DB group (20 patients) and the SB group (20 patients). Four-stranded semitendinosus and gracilis autologous grafts were used in the SB group and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 27 publications
3
93
0
2
Order By: Relevance
“…Their main finding was that contrary to their hypothesis there was no significant difference between the SB and the DB group regarding stability or knee evaluation forms. Sastre et al [43] had similar results in their study at the two-year followup. Aglietti et al [44] reported two-year results in 2010.…”
Section: Randomised Controlled Studiessupporting
confidence: 57%
“…Their main finding was that contrary to their hypothesis there was no significant difference between the SB and the DB group regarding stability or knee evaluation forms. Sastre et al [43] had similar results in their study at the two-year followup. Aglietti et al [44] reported two-year results in 2010.…”
Section: Randomised Controlled Studiessupporting
confidence: 57%
“…The 'double bundle debate' [40,43] has opened the door to a greater understanding of native anatomy, and newer techniques have been investigated to improve the outcome following ACL reconstruction [25,46]. The evolution of anatomic ACL reconstruction has focused on changing the femoral tunnel position from the traditional high '11 o'clock' notch position [32] to the more anatomic mid-bundle position within the ACL footprint [19].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our rationale for developing the rounded rectangle dilators was the ability of the rounded rectangle tunnels to more closely mimic the femoral footprint (compared to the rounded tunnels). In addition, Ho et al [18] and Sastre et al [10] have reported that anatomical single bundle ACL reconstruction and double bundle ACL reconstruction provide very similar stability. Thus, attention has returned to single bundle reconstruction with the graft placed at the center of the anatomical position.…”
Section: Discussionmentioning
confidence: 98%
“…Several recent biomechanical studies have shown that single bundle ACL grafts that are placed in the center of their anatomic insertions can provide nearly normal knee kinematics, which are comparable to double bundle ACL reconstruction [10] . In 2010, we began performing anatomical single bundle ACL reconstruction with a navigation system, and have successfully restored good knee stability for most of our patients.…”
Section: The Anatomical Double Bundle Acl Reconstruction Technique Wamentioning
confidence: 99%